Instructional design: urgensi kurikulum budaya berbasis muatan lokal kabupaten Lembata Nusa Tenggara Timur - Cholily, Yus Mochamad; Baiduri, Baiduri; Restian, Arina; Suwandayani, Beti Istanti; Deviana , Tyas; Kuncahyono; Herviani, Vivi Kurnia (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
Local content learning has yet to be fully implemented administratively in Lembata District. This condition is because Lembata Regency has a variety of cultures in each District. Several examples of the use of regional languages have a type with unique and distinctive nuances. This research aims to produce a curriculum set product equipped with a lesson plan (RPP) that accommodates learning in the context of local culture. This research is a research and development with the ASSURE model. The test subjects (users) in this study were teachers and fourth-grade students at SD Naga Wutung District, Lembata Regency. Data was collected using a curriculum expert validation questionnaire and a test questionnaire for users (teachers and students). The results of the data findings were then processed and analyzed descriptively. Based on the validation results of curriculum experts, a score of 83% was obtained with valid criteria and feasible to use. Based on user trials (teachers and students), a score of 85% was obtained with applicable standards but needed to be supplemented with other teaching media in the form of technology-based media. Implementing Lembata District's culture-based curriculum implies that teachers can implement learning and develop learning tools based on cultural curriculum offerings under the applicable curriculum.  Keyword: Independent Curriculum; Cultural Curriculum; Local Content; Lembata Regency; East Nusa Tenggara